Pemberdayaan Pengelola Wisata Curug Silawe Berbasis Aksi Lingkungan dan Promosi Digital - Almahmud, Muhammad Risfie; Septiana, Dela; Ranti, Susiana Sofia; Filmanda, Betha Carrisa; Nugroho, Hendra Aji; Maulana, Wildan; Nugraha, Joko Tri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Curug Silawe in Magelang Regency has promising natural tourism potential, but still faces problems with cleanliness and suboptimal digital promotion. These conditions have an impact on the instability of tourist visitation numbers, so community empowerment activities that are in line with field needs are required. This initiative aims to assist managers in improving the cleanliness of the area while strengthening promotion through social media to increase awareness and interest in Curug Silawe. The program was implemented in collaboration with managers as key partners, beginning with observation and discussion, followed by cleanup activities and the creation of visual content for publication on social media. The results of the activities showed significant changes, marked by a reduction in trash, a tidier area, and positive responses to promotional posts on Instagram. These findings indicate that simple collaboration with managers can improve environmental conditions and the image of the destination, and therefore needs to be supported on an ongoing basis.